Answer:
The answer is 1.
Explanation:
The other solution is correct and good. I would like to show a different substitution and how it ends up with a different solution.
x/sqrt(x^2+1) = sqrt (x^2/(x^2+1))
=sqrt(1/(1+1/x^2))
=1/sqrt(1+1/x^2)
let x be cotΘ
dx=-csc^2ΘdΘ
1/x^2 = 1/cot^2Θ = tan^2Θ
x/sqrt(x^2+1)dx = 1/sqrt(1+1/x^2)dx
=1/sqrt(1+tan^2Θ) * (-csc^2Θ)dΘ
=-1/sqrt(sec^2Θ) * csc^2ΘdΘ
=-1/secΘ * csc^2ΘdΘ
=-cosΘ.csc^2ΘdΘ
I =
![\int\ -cos\theta\csc^2\theta\ \, d\theta\](https://img.qammunity.org/2019/formulas/mathematics/middle-school/aomm4gggdlbtwyntjgeb1k99y832n7kdmr.png)
if plotted together, it is the same curve as for 1 but with Θ shifted by pi/2.